1987
DOI: 10.1002/hep.1840070316
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ciprofibrate and clofibric acid as peroxisomal proliferators in primary cultures of rat hepatocytes

Abstract: We have determined the comparative activities of peroxisomal proliferators, ciprofibrate and clofibric acid on various hepatic parameters associated with endoplasmic reticulum, mitochondria and peroxisomes in primary cultures of rat hepatocytes. We have measured the activities of carnitine acetyltransferase and fatty acylCoA oxidase, and the amount of 60 and 80 kD polypeptides as biochemical markers of the peroxisomal function; laurate hydroxylase and cytochrome P-450 as markers of the endoplasmic reticulum; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated that fatty acids and peroxisomal proliferator compounds, such as clofibrate (a ligand for PPAR␣), stimulate transcription of L-CPT I gene (Feller et al, 1987;Gerondaes et al, 1988;Brady and Brady, 1989;Brady et al, 1991). Thus, the gene encoding CPT I probably represents a PPAR␣ target gene.…”
Section: Regulation Of Carnitine System Enzyme Activitymentioning
confidence: 97%
“…Several studies have demonstrated that fatty acids and peroxisomal proliferator compounds, such as clofibrate (a ligand for PPAR␣), stimulate transcription of L-CPT I gene (Feller et al, 1987;Gerondaes et al, 1988;Brady and Brady, 1989;Brady et al, 1991). Thus, the gene encoding CPT I probably represents a PPAR␣ target gene.…”
Section: Regulation Of Carnitine System Enzyme Activitymentioning
confidence: 97%